Unchained, Yet Prosecuted – Victims of Human Trafficking as Subjects of Criminal Liability and Art. 4 of the ECHR - Čep , David; Provazník, Jan (The ECHR at 70: The Central European Narrative, 2025)
This paper examines the complex legal issue of criminal liability for victims of human trafficking under Article 4 of the European Convention on Human Rights (ECHR). The study addresses the tension between protecting trafficking victims from prosecution for crimes they were compelled to commit during their victimization and maintaining the integrity of criminal law systems. It analyzes the regulatory framework surrounding human trafficking, including the Warsaw Convention, the Palermo Protocol, and EU Directive 2011/36/EU, all of which provide for the possibility of non-prosecution or non-penalization of trafficking victims under specific circumstances. Through examination of recent European Court of Human Rightscase law, particularly “V.C.L. and A.N. v. the United Kingdom” and “G.S. v. the United Kingdom”, the paper demonstrates that neither international instruments nor ECHR jurisprudence establish absolute immunity for trafficking victims.The author proposes a comprehensive two-step assessment framework for determining when non-prosecution obligations apply. First, victim status must be established through proper investigation by specialized authorities. Second, five critical factors must be evaluated: (I) the nexus between the crime and victim status, (II) the intensity of coercion, (III) reasonably expected consequences of non-compliance, (IV) the victim's personal situation and trafficking context, and (V) the nature and severity ofthe committed crime. The paper argues that the non-prosecution requirement should be understood as a standalone negative obligation under Article 4 ECHR rather than merely a component of positive protective obligations. This approach would provide clearer legal boundaries while preventing potential expansion to other victim categories. The research concludes that criminal prosecution of trafficking victims does not automatically violate Article 4 ECHR, but requires careful case-by-case analysisbalancing victim protection with other legitimate interests, including the rights of crime victims and public safety concerns.Keywords: human trafficking; criminal liability; victim immunity; ECHR Article 4; positive obligations; non-prosecution